Visual Analysis and the application of Islamic law in farm animal vocabulary learning videos for children - Pertiwi, Annisa Bela; Budiman, Budiman; Iskandar, Asep Deni; Supandi, Fajar Persada (International Journal of Visual and Performing Arts, 2024)
This study analyzes the visual expression and application of Islamic legal principles, particularly iqtina ash-shurah, in the animated video "Learning Vocabulary: Names of Farm Animals" produced by Yufid Kids. This video serves as an educational medium for early childhood learners to acquire vocabulary related to farm animals. The study is important as it addresses the intersection of Islamic legal principles and visual media, providing a framework for creating educational content that aligns with sharia while remaining engaging and effective. The content of the wimba used is a visual representation of livestock depicted in a simple and unrealistic way, adhering to sharia principles and avoiding realistic depictions of living beings. Visual expressions in the video consist of four types: first, expressing space, which clearly displays the location and environment of animals; second, expressing motion, which includes animations that illustrate animal activities, making it easier for children to grasp vocabulary; third, external expressions that indicate time and space through scene transitions, facilitating contextual shifts in the narrative; and finally, stating importance, which emphasizes key information through visual elements such as color and size to draw attention to essential learning components. From the perspective of Islamic law, the analysis focuses on the application of iqtina ash-shurah, which permits the use of simplified and non-detailed images of living beings, and the inclusion of thayyibah sentences to reinforce Islamic values. The research uses a qualitative descriptive method through visual and sharia analysis. The findings demonstrate that the video successfully integrates effective visual expressions with adherence to Islamic principles, providing an interactive, educational, and Islamic learning experience. This research contributes to the field of Islamic education and visual media by offering a model for developing sharia-compliant educational content, highlighting the theoretical and practical value of visual expressions in reinforcing Islamic values in early childhood learning.